PENGUATAN DUKUNGAN KELUARGA PADA PENGENDALIAN FAKTOR RISIKO PJK YANG DAPAT DIMODIFIKASI PADA PEREMPUAN DEWASA - Rodiyatun Rodiyatun; Fitriah Fitriah; Suryaningsih Suryaningsih; Mustofa Haris (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2021)
Introduction: Coronary Heart Disease (CHD) is a condition when the main blood vessels that supply blood, oxygen, and nutrients to the heart become damaged. Women are more susceptible to CHD, because of more complexity comorbidities including pregnancy, oral contraceptives, hormone therapy and obesity. These comorbidities trigger hypertension which ends in CHD. Psychological factors associated with dual roles as wife, mother, and worker, make women more at risk of experiencing mental stress that triggers CHD. Family involvement and support are critical aspects of women's success in controlling CHD risk factors. The aim of the study was to analyze the effect of family support on controlling modifiable CHD risk factors in women. Methods: This type of research is analytic observational, cross sectional design. The population is family in Bangkalan Regency, spread over 273 villages/urban villages, the sampling technique is Cluster Random Sampling based on regional characteristics. Number of sample is 350. Data collection is using questionnaire. Analysis and Results: The first stage of analysis uses Smart PLS software, the second stage uses Wilcoxon. The test results show that family support has a significant effect on controlling CHD risk factors. Discussion and conclusion: The research findings are, Family support is a potential that needs to be strengthened in controlling disease risk factors. Strengthening concrete support from the family make great potential for women's behavior to control CHD risk factors.